Le métier d’enseignant : formation professionnelle et formation des talents - Umberto Margiotta (Recherches en Éducation)
The masterization process of initial teacher training, in Italy and in France, settles strong façon in the problem of links between teacher training and educational research. For us the monster crucial question is that a new compass is essential. The latter cannot be made up only by one theory of the intelligence in formation. If one wants to make flexible, economic and expert the formative offer, and to support the personalization of learning, the processes and the products of training, then it is necessary, from a point of view of education, to ensure the formation and the development of the talents. That gives effectiveness of the teachers. By consequence the professionality of the teacher, or its teaching action and not only didactic, is in any point similar (in term of risks, oblativity, aspect determining of its acts) to that of a doctor. Like the doctor of the life, the teacher is responsible for the spirit of his pupils; if the diagnosis is a strategic act for the doctor, in term of intervention and treatment, it is it also for teaching under educational diagnosis